Gender and tourism: gender, age and mountain tourism in Japan - Michihiko Nakata,; Janet D Momsen, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2010)
A new form of tourism is sweeping Japan. Groups of middle-aged women, mostly aged between fifty and seventy, are collecting mountain summits. They hike up mountains in organized groups on one to four-day expeditions. It is not unusual in Japan for men and women to undertake leisure activities separately but hiking up mountains, as contrasted to mountaineering, is definitely a hobby of women. We hypothesize that Japanese women of this older generation are fitter and live longer than previous generations and have reached an age when they have both the time and money to undertake these activities. Reaching the summit is often celebrated with relaxing in baths fed by hot springs. The authors link this new form of tourism to the pilgrimages to sacred sites, often associated with mountains, popular in eighteenth century Japan.